Представьте, что вы сворачиваете двумерный массив в одномерный массив:
int arr2D[2][3];
int arr1D[2 * 3]; // # of rows * # of columns
// access element [1][2] of 2D array, i.e., the last element
int elem2D = arr2D[1][2];
// access element [1][2] of 1D array, i.e., the last element
int elem1D = arr1D[1 * 3 + 2];
// =========================================================
lets visualize the array access:
arr2D => x/y 0 1 2
0 [N][N][N]
+1 on x > 1 [N][N][N]
+2 on y ---------- ^
y_len => ^-------^ 3 elements
so the access happens with x * y_len + y
1 * 3 + 2
now for the 1D array
we want the second row, so we go with 1 * 3
(0-based access, y_len = 3)
and then we want the 3rd element, so + 2
(again, 0-based access)
arr1D => x 0 1 2
[N][N][N]
3 4 5
1 * 3 = 3 > [N][N][N]
+ 2 = 5 ---- ^
Надеюсь, я не сделал это слишком сложным (хотя я думаю, что сделал ...).:)